Penggunaan Model Pair Check Berbantuan Kartu Soal Untuk Meningkatkan Prestasi Belajar Materi Lingkaran - Rahaju Rahaju; Dias Wahyulina; Riski Nur Istiqomah Dinullah (RANGE: Jurnal Pendidikan Matematika, 2024)
Negative perceptions of mathematics cause students to be lazy, uninterested and even refuse to study mathematics, resulting in low student achievement. The aim of this research is to describe the steps for learning pair check with the help of question cards to improve learning achievement in circle material. This research is classroom action research. The research subjects were 30 class VIII students at SMPN 2 Turen. Data collection uses observation, documentation and test techniques. The research instruments used observation. Sheets, field notes, photo and video documents, and test. The research results show that pair check learning begins by assigning students to study reading material individually, then solve problems in groups of 4 students. Next, give question cards to be completed in small groups (2 students). In small groups, students take turns playing the role of partner and coach in solving the questions card. Discussion of question answers is carried out classically through presentation activities. Student learning achievement using the pair check model assisted by question cards has increased. In cycle 1, 70% of students had completed their studies. The results of this research are expected to provide alternative stages and learning media that can improve student learning achievement.